Histone Lysine Methyltransferase SDG8 Is Involved in Brassinosteroid-Regulated Gene Expression in Arabidopsis thaliana - Wang, Xiaolei; Chen, Jiani; Xie, Zhouli; Liu, Sanzhen; Nolan, Trevor; Ye, Huaxun; Zhang, Mingcai; Guo, Hongqing; Schnable, Patrick S.; Li, Zhaohu; Yin, Yanhai (My University, 2014)
The plant steroid hormones, brassinosteroids (BRs), play important roles in plant growth, development and responses to environmental stresses. BRs signal through receptors localized to the plasma membrane and other signaling components to regulate the BES1/BZR1 family of transcription factors, which modulates the expression of 4,000-5,000 genes. How BES1/BZR1 and their interacting proteins function to regulate the large number of genes are not completely understood. Here we report that histone lysine methyltransferase SDG8, implicated in Histone 3 lysine 36 di- and tri-methylation (H3K36me2 and me3), is involved in BR-regulated gene expression. BES1 interacts with SDG8, directly or indirectly through IWS1, a transcription elongation factor involved in BR-regulated gene expression. The knockout mutant sdg8 displays a reduced growth phenotype with compromised BR responses. Global gene expression studies demonstrated that SDG8 plays a major role in BR-regulated gene expression as more than half of BR-regulated genes are differentially affected in sdg8 mutant. A Chromatin Immunoprecipitation (ChIP) experiment showed that H3K36me3 is reduced in BR-regulated genes in the sdg8 mutant. Based on these results, we propose that SDG8 plays an essential role in mediating BR-regulated gene expression. Our results thus reveal a major mechanism by which histone modifications dictate hormonal regulation of gene expression.
Citation: Wang, X., Chen, J., Xie, Z., Liu, S., Nolan, T., Ye, H., et al. (2014). Histone lysine methyltransferase SDG8 is involved in brassinosteroid- regulated gene expression in arabidopsis thaliana.
Keywords: Brassinosteroid; Histone modifications; Gene regulation